Gen‐Z memory pool system implementation and performance measurement. Issue 3 (30th November 2021) - Kwon, Won‐ok; Sok, Song‐Woo; Park, Chan‐ho; Oh, Myeong‐Hoon; Hong, Seokbin
Abstract: The Gen‐Z protocol is a memory semantic protocol between the memory and CPU used in computer architectures with large memory pools. This study presents the implementation of the Gen‐Z hardware system configured using Gen‐Z specification 1.0 and reports its performance. A hardware prototype of a DDR4 Gen‐Z memory pool with an optimized character, a block device driver, and a file system for the Gen‐Z hardware was designed. The Gen‐Z IP was targeted to the FPGA, and a 512 GB Gen‐Z memory pool was configured on an ×86 server. In the experiments, the latency and throughput of the Gen‐Z memory were measured and compared with those of the local memory, SATA SSD, and NVMe using character or block device interfaces. The Gen‐Z hardware exhibited superior throughput and latency performance compared with SATA SSD and NVMe at block sizes under 4 kB. The MySQL and File IO benchmark of Gen‐Z showed good write performance in all block sizes and threads. Besides, it showed low latency in RocksDB's fillseq dbbench using the ext4 direct access filesystem.